The Cotton-Textile Circuit in Formosa, Argentina 2003-2015 - Sapkus, Sergio Omar; Giuliano, Ernesto Fabian (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper analyzes the subnational public policy in Argentina. Specifically, the state intervention in Formosa is studied, a province of the lagging periphery, differentiated by its low economic dynamism and historically marginalized in the national socio-spatial configuration. It is intended to show that, despite the “postneoliberal” turn of the Argentinian state in the period considered, the local/regional policies implemented in Formosa follow a neoliberalizing course. We take as a specific case study the policy followed around a sector/territorial intervention on some links of the cotton-textile chain based in the province between 2003 and 2015. We concluded that, based on the ideas of New Regional Orthodoxy, the regional public policy is oriented to impose market discipline by state channels, keeping subordinated political and social agendas to the priority of maintaining investor confidence and the good climate business, territorial competitiveness and flexible labor market.